Reversal of the Rights and Obligations of Gender Equality (Case Study of Rights, Participation in the Discrimination of Female Workers in Cigarette Factory in Malang City) - Muhammad Husni; Fitriyah Mahdali; Ashila Rahmani (HUMANISMA : Journal of Gender Studies, 2023)
Changes in people's behavior towards women's lack of equality and human rights Women as a whole have not been able to gain the right to grow and equate with men. Women tend to become marginalized individuals and become subordinate to men. We know why many cigarette factories employ women as laborers, while men are employed in important roles such as corporate managers, overseers, and staff of tobacco companies. So why are there so many women who are placed as workers or regular employees? This indicates a lack of equality for women, and always assume that man is still regarded as a strong figure and responsible for finding and positioning the company or factory. Whereas women are weaker figures assigned to organize and as ordinary employers may even be merely appropriate for household affairs. When women enter the world of work, they are still faced with disenchanted behavior and a lack of justice for equality between men and women. In the competition of the working world, women are also in the lowest position compared with men. It is needed to give women opportunities to get equal access to men. This goal can be realized if the regulations made by the state are carried out properly and if the company is committed to giving fair treatment to women, eliminating gender discrimination, and providing human rights and equality between men and women.